A Specific, Glycomimetic Langerin Ligand for Human Langerhans Cell Targeting - Wamhoff, Eike-Christian (ACS Cent Sci, 2019)
[Image: see text] Langerhans cells are a subset of dendritic cells residing in the epidermis of the human skin. As such, they are key mediators of immune regulation and have emerged as prime targets for novel transcutaneous cancer vaccines. Importantly, the induction of protective T cell immunity by these vaccines requires the efficient and specific delivery of both tumor-associated antigens and adjuvants. Langerhans cells uniquely express Langerin (CD207), an endocytic C-type lectin receptor. Here, we report the discovery of a specific, glycomimetic Langerin ligand employing a heparin-inspired design strategy and structural characterization by NMR spectroscopy and molecular docking. The conjugation of this glycomimetic to liposomes enabled the specific and efficient targeting of Langerhans cells in the human skin. We further demonstrate the doxorubicin-mediated killing of a Langerin(+) monocyte cell line, highlighting its therapeutic and diagnostic potential in Langerhans cell histiocytosis, caused by the abnormal proliferation of Langerin(+) myeloid progenitor cells. Overall, our delivery platform provides superior versatility over antibody-based approaches and novel modalities to overcome current limitations of dendritic cell-targeted immuno- and chemotherapy.